ISSUES OF PROTECTION, PRESERVATION AND PROMOTION OF INTANGIBLE CULTURAL HERITAGE (Modern education and development, 2025)
Our state attaches great importance to the development of this sector. And it is the decision of the leadership of our state “On the development and additional measures to improve the preservation, scientific study and promotion of the intangible cultural heritage” that is extremely comprehensive, and first of all, our intangible cultural heritage further expansion. serves as a real upgrade program. Also, on the basis of the decision, starting from 2024, every year in March, the “Month of National Values” product and folk entertainments were launched; On October 20, 2014, until October 1, the “Qadriyat” electronic platform and its mobile application were created and integrated with relevant electronic access and resources. I think that this kind of help pays off.